P13 The relationship between homeworking and m health and wellbeing before and during the Covid-19 pandemic: a systematic review. (26th August 2022) - Goyder, Elizabeth; Blank, Lindsay; Hock, Emma; Cantrell, Anna
Abstract : Background: Understanding the impact of working from home on health and wellbeing is of great interest to employers and employees alike, with a strong need for up-to-date guidance. The aim of this review was to identify, appraise and synthesise existing research evidence that explores the impact of home working on health and wellbeing outcomes for working people and health inequalities in the population. Methods: We searched databases, reference lists, UK grey literature; and completed citation searching of included papers. We extracted and tabulated key data from the included papers and synthesised narratively. Associations reported in the literature were displayed by constructing mind maps of each individual association which had been identified. The findings were combined with an a priori model to develop a final model, which was validated in consultation with stakeholders. Results: Of 96 studies which were found to meet the inclusion criteria for the review, 30 studies were published before the Covid-19 pandemic and a further 66 were published during the pandemic. The quality of evidence was limited by the study designs employed by the authors with the majority of studies being cross sectional surveys (n=59). Fifteen studies which considered the potential for working at home to have different effects for different subgroups suggested that working at home may have more negative consequences during the Covid-19 pandemic for women and in particular, mothers. There was very little evidence on age, ethnicity, education or income in terms of moderating home working effects, and very limited evidence from before the Covid-19 pandemic. The concept of lack of choice around working from home was implicit in much of the literature– even though it was not directly measured. There were no clear patterns of wellbeing measures which changed from positive to negative association (or vice versa) during the pandemic. Conclusion: The evidence base for the associations between home working and health-related outcomes has expanded significantly as a result of the need for those whose work could be done from home to work at home during the Covid-19 pandemic. Our findings suggest that there are three sets of factors relating to the external context, the role of employers, and the circumstances of the employee which contribute to determining whether someone works at home and what the associated impacts on health and wellbeing may be.